Power system stability enhancement in the presence of renewable energy resources and HVDC lines based on predictive control strategy. (September 2016) - Darabian, M.; Jalilvand, A.; Azari, M.
Abstract: The renewable energy resources are increasingly employed as new electric power sources. However, their stochastic and uncertain behavior negatively influences the power system stability. In this paper, a hybrid system composed of PMSG-based wind farm, marine-current farm, and PV has been used to supply the network's load. These resources have been connected to a nine-bus power system through a line-commutated HVDC link. A new control method has been proposed to enhance the damping characteristics of power system. This method is based on Generalized Predictive Control (GPC) for design of inverter current regulator (ICR) of HVDC link. In this regard, the BAT search algorithm has been employed for obtaining the best solution for the GPC's objective function. In order to demonstrate the effectiveness of the proposed GPC-BAT method, the simulations using eigenvalue analysis and root-loci technique are presented. For further investigating the efficiency of conducted approach, a PID controller has been designed for controlling the ICR of HVDC link, and the results have been compared with those of GPC-BAT method. The comparisons have been made through a three-phase short circuit fault on the multi-machine power system in MATLAB software. The evaluations clearly show the effectiveness and superiority of the proposed approach.